Investigation of Unilateral Mandibular Coronoid Hyperplasia Cases Using Cone Beam Computed Tomography - Ersen Bilgili (Van Tıp Dergisi, 2017)
INTRODUCTION: Hyperplasia of Mandibular Coronoid Process (HMCP) is first described by Langenbeck in 1853. Cases are mostly seemed bilateral therefore unilateral ones may exist. Aim of this retrospective study is; to evaluate the vertical measurements statistically of the coronoid and condylar processes in hyperplasia seen and unseen sides in unilateral HMCP cases whose cone beam computed tomography (CBCT) images are taken for different reasons. METHODS: Unilateral HMCP in 32 of 502 patients whose CBCT images were taken for different reasons is analyzed. In boths hyperplasia forseen and unseen sides of each patient; coronoid length, condyl length and the ratio between them statistically evaluated. RESULTS: According to measurements, In hyperplasia seen sides of the patients; avarage length of coronoid process was 15,72 mm (+- 0,40), avarage length of the condylar process was 13,23 mm (+- 0,51) and the ratio between them was calculated 1,24. Avarage length of coronoid process was 13,75 mm (+- 0,33), avarage length of the condylar process was 15,32 mm (+- 0,39) and coronoid/condylar length ratio was 0,90 in the normal side. According to results of t test; with the value of p= 0,023 (p<0,05) the difference between coronoid/condylar process ratios was significant. DISCUSSION AND CONCLUSION: CBCT is available for evaluation of HMCP.